Analisis Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) Dan Gross Profit Margin Untuk Mengukur Kinerja Keuangan Pada PT Raje Baginda Jurai Di Palembang - Kemas Welly Angga Permana; Roy Saleh; Nelly; Lia Sari; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this research is to assess and analyze financial performance in terms of profitability ratios in the form of Return on Assets, Return on Equity, Net Profit Margin and Gross Profit Margin at PT Raje Baginda Jurai in Palembang for the period 2018 to 2020. This research uses a descriptive approach, which is a study that only collects, compiles, classifies and interprets data so that it can fulfill a clear picture of the problem being studied. The results of the analysis and discussion show the financial performance of PT Raje Baginda Jurai in Palembang in terms of profitability ratios in the form of Return on Assets has poor financial performance because the company is less able to use large assets effectively and efficiently to generate maximum profit. For financial performance in the form of Return on Equity, it is below the standard average. This is due to high capital but not being able to generate maximum profit. The company's Net Profit Margin has a fairly good performance, this is because even though sales are declining, profits are still increasing, although not significantly. And financial performance in the form of Gross Profit Margin has a pretty good performance. Where the company is able to reduce operational costs and taxes so that it can still generate profits.